Influence of method of preparation on the activity of La-Ni-Ce mixed oxide catalysts for dry reforming of methane - Sagar, T. V.; Sreelatha, N.; Hanmant, G.; Surendar, M.; Lingaiah, N.; Rao, K. S. Rama; Satyanarayana, C. V. V.; Reddy, I. A. K.; Prasad, P. S. Sai (RSC Advances, 2014)
La-Ni-x-Ce1-x mixed oxide catalysts were prepared by a sol-gel method varying the Ni composition (0 <= x <= 1). The catalysts were characterized by X-ray diffraction (XRD), inductively coupled plasma optical emission spectroscopy (ICP-OES), BET surface area, X-ray photoelectron spectroscopy (XPS), temperature-programmed reduction (TPR), H-2 chemisorption and Fourier transform infrared spectroscopy (FT-IR) techniques. CO2 reforming of methane was carried out at atmospheric pressure and 800 degrees C, maintaining a reactant CO2/CH4/N-2 ratio of 80/80/80 (total flow rate = 240 ml min(-1), GHSV of 28 800 h(-1)). The catalysts offered higher activity even at lower Ni compositions. LaNi0.4Ce0.6O3. showed the highest conversion of CH4 and CO2. The H-2/CO ratio in the syngas was stable at 0.85 +/- 0.02. The performance of the sol-gel catalysts was compared with that of the hydrothermally prepared catalysts, reported earlier. High surface area and better Ni dispersion were found to be the reasons for superior activity of the sol-gel catalysts.